2019
DOI: 10.1515/gps-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

Azadirachta indica leaves extract assisted green synthesis of Ag-TiO2 for degradation of Methylene blue and Rhodamine B dyes in aqueous medium

Abstract: Aqueous pollution due to textile industry is an important issue. Photocatalysis is one of the methods used for eradication of dyes from textile industrial effluents. In this study, the synthesis, characterization and evaluation of photo catalytic activity of Ag-TiO2 is reported. TiO2 catalysts with 2, 4, 6 and 8% loading of Ag were prepared by green methods using Azadirachta indica leaves extract as reducing agent with titanium dioxide and silver nitrate as precursor materials. Prepared catalyst was characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Activation energy (Ea) was determined as 20.6 kJ/mol using the Arrhenius plot ( Figure 5 c). The data obtained were consistent with the results of previous studies where the Ea was reported as 27.1 and 25.7 kJ/mol for 0.1 g Ag-TiO 2 [ 59 ] and 0.1 g of 3% Ag/Al 2 O 3 [ 61 ] composites, respectively. As an advantage, the results in our study indicated a lower activation energy.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Activation energy (Ea) was determined as 20.6 kJ/mol using the Arrhenius plot ( Figure 5 c). The data obtained were consistent with the results of previous studies where the Ea was reported as 27.1 and 25.7 kJ/mol for 0.1 g Ag-TiO 2 [ 59 ] and 0.1 g of 3% Ag/Al 2 O 3 [ 61 ] composites, respectively. As an advantage, the results in our study indicated a lower activation energy.…”
Section: Resultssupporting
confidence: 92%
“…Based on the data obtained, it can be noted that an increase in dye concentration caused a decrease in decomposition efficiency for two reasons. First, the concentrated solution acquired a more intense color that prevented the penetration of radiation onto the catalyst surface [ 59 ]. Second, as other experimental conditions were the same, the ratio of the number of hydroxyl radicals, •OH, to the number of dye molecules decreased with increasing concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The silver (Ag) doping is used for improvement of photocatalytic performance of titanium dioxide towards photo degradation of organic pollutants [34][35][36]. Saeed et al, [37] have reported the improvement in photocatalytic performance of titanium dioxide for photodegradation of methylene blue and rhodamine B dyes by incorporation of silver (Ag) in the structure of titanium dioxide. They investigated the effect of silver (Ag) on the photocatalytic performance of titanium dioxide using 2, 4, 6, and 8% loading of Ag on titanium dioxide.…”
Section: Dopingmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) has been widely exploited as an efficient photocatalytic semiconductor for the photo-oxidation of a vast variety of organic contaminants because of its low cost, low toxicity, abundance, photo-corrosion resistance, thermal and chemical stability and high oxidation ability [1]. Because of its relatively wide band gap and low separation efficiency of photo-generated charge carrier, enormous efforts have been made to improve the photocatalytic activity of TiO 2 like nonmetal [2] and metal [3] doping, dye sensitization [4], defect engineering [5] and constructing hierarchical structures [6].…”
Section: Introductionmentioning
confidence: 99%